Belarusian State University students’ marriage and family attitudes - Kurilovich, Natalia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article analyzes the results of sociological research conducted by the method of questionnaire in 2016. The author examines the attitude of students of the Belarusian state university to the official registration of marriage and cohabitation; the opinion of the students’ youth on the most favorable age for marriage, and important for them qualities of a life partner. Special attention is paid to the views of young people about models of family relationships (distribution of responsibilities between spouses, the combination of family and career, making important family decisions). The article is devoted to the reproductive attitudes of students. The author shows the students’ attitude towards parenthood (presence of knowledge about conscious parenthood, the most interesting issues related to parenthood, preferred models of parenting).